2015
DOI: 10.1142/s0218625x15500225
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Biomolecules With Nanostructured Porous Silicon for Biomedical Application

Abstract: Porous silicon (PS) fabrication, changes in the optical properties and surface modi¯cation in the oxidized PS (dipped into the Glucose oxide) due to the in¯ltration of biomolecules using Luminescence Spectrophotometer [Photoluminescence (PL)], Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscope (SEM) were studied. The surface morphology of oxidized PS (OPS) and treated with Glucose have been studied by SEM. Spontaneous imbibition weight was calculated theoretically using imbibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…PNMs are nanomaterials with a porous structure and high surface ratio, which are widely used in the fields of biomedical engineering [14][15][16][17][18] such as bone regeneration [18][19][20][21], drug delivery [22][23][24], cell trace, and regulation of cell differentiation. Since 2014, it has been reported that mesoporous bioactive glass nanomaterials can promote osteogenic differentiation through activation of autophagy [25].…”
Section: Introductionmentioning
confidence: 99%
“…PNMs are nanomaterials with a porous structure and high surface ratio, which are widely used in the fields of biomedical engineering [14][15][16][17][18] such as bone regeneration [18][19][20][21], drug delivery [22][23][24], cell trace, and regulation of cell differentiation. Since 2014, it has been reported that mesoporous bioactive glass nanomaterials can promote osteogenic differentiation through activation of autophagy [25].…”
Section: Introductionmentioning
confidence: 99%